2021
DOI: 10.1109/tii.2021.3071405
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Autonomous Driving Systems: A Survey of Attacks and Defenses

Abstract: The rapid development of artificial intelligence, especially deep learning technology, has advanced autonomous driving systems (ADSs) by providing precise control decisions to counterpart almost any driving event, spanning from anti-fatigue safe driving to intelligent route planning. However, ADSs are still plagued by increasing threats from different attacks, which could be categorized into physical attacks, cyberattacks and learningbased adversarial attacks. Inevitably, the safety and security of deep learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…Before this paper, a few AD security-related surveys have been published [20][21][22][23], but none of them focus on the emerging semantic AD AI research space (i.e., our scope defined in §II-C). For example, Kim et al [20] and Ren et al [21] focus on AD-related sensor/hardware security and in-vehicle network security, instead of AD AI components.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Before this paper, a few AD security-related surveys have been published [20][21][22][23], but none of them focus on the emerging semantic AD AI research space (i.e., our scope defined in §II-C). For example, Kim et al [20] and Ren et al [21] focus on AD-related sensor/hardware security and in-vehicle network security, instead of AD AI components.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Kim et al [20] and Ren et al [21] focus on AD-related sensor/hardware security and in-vehicle network security, instead of AD AI components. Qayyum et al [23] and Deng et al [22] touched upon the security of AI components in AD, but did not focus on the works that addressed the semantic AI security challenges (e.g., most of the included works are on generic AI and sensor security without studying impacts on AD AI behaviors). In fact, Deng et al [22] considers the semantic AD AI security as a future direction.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as various sensors for detecting the outside world, the vehicle will be equipped with on-board computer processors and electronic-oriented memory technology, and can communicate with the cloud via a communication device [363]. Besides data communication, edge-cloud collaborative learning techniques will further enhance autonomous driving on safety, functionality, and privacy [364]. Initially trained on clouds, edge machine learning models (cloud → edge) can interpret real-time raw data, make decisions based on the derived insights, and learn from the feedback from real-time road conditions.…”
Section: Auto-drivingmentioning
confidence: 99%
“…Although the image classification model provides great convenience for users, the inherent fragile of deep learning is a weakness of the service. Recent studies [12,13] have shown that an attacker can create adversarial samples by adding small disturbances to the original data. e disturbances are very small, and they are almost invisible to the human eye.…”
Section: Introductionmentioning
confidence: 99%